Konsep Penataan Ruang Publik Area Gapura Kelurahan Curug Kota Bogor - Rahmat Rejoni; Andrianto Kusumoarto; Enik Kristiana (Lakar: Jurnal Arsitektur, 2023)
The rapid development of the City of Bogor has encouraged the local government to organize public spaces for the people in their area. Curug Village, especially in RW 07, has an area for P2WKSS (Increasing the Role of Women towards Healthy and Prosperous Families) activities. There is an area that needs to be arranged to support the program, namely the gate area as the entrance to RW 07. This area is a former street vendor area. The Curug Kelurahan government wants a public space that has an optimal function to accommodate community and local government activities and has good environmental aesthetic values. The purpose of this activity is to arrange public space in the gate area of RW 07, Curug Village, Bogor City. The method used for this activity is a qualitative descriptive method in landscape planning and design with an expert and public participatory approach. The stages in carrying out this activity are 1) Interview with the Housing and Settlements Office and Kelurahan Curug, Bogor City, 2) Determination of the boundaries of the planning and design area, 3) Site survey and mapping, 4) Site inventory, 5) Site analysis, 6) Planning and site design. The results obtained are design with the concept of a park as a public space, with zoning divisions in the form of space for services, recreation space, and green space. The results of the concept that has been made are expected to help the waterfall village, especially RW 07 in participating in the competition.